Polyion complex (PIC) particles: Preparation and biomedical applications. (August 2016) - Insua, Ignacio; Wilkinson, Andrew; Fernandez-Trillo, Francisco
Graphical abstract: Abstract: Oppositely charged polyions can self-assemble in solution to form colloidal polyion complex (PIC) particles. Such nanomaterials can be loaded with charged therapeutics such as DNA, drugs or probes for application as novel nanomedicines and chemical sensors to detect disease markers. A comprehensive discussion of the factors affecting PIC particle self-assembly and their response to physical and chemical stimuli in solution is described herein. Finally, a collection of key examples of polyionic nanoparticles for biomedical applications is discussed to illustrate their behaviour and demonstrate the potential of PIC nanoparticles in medicine.